Encapsulation of bioactive peptides derived from Sargassum angustifolium algae using calcium alginate and chia gum - Sara Jafarirad; Leila Nateghi; Masoumeh Moslemi; Kian Pahlevan Afshari; Kianoush Khosravi-Darani (Food Chemistry: X, 2025)
This study aimed to encapsulate bioactive peptides derived from Sargassum angustifolium protein isolate within calcium alginate and chia seed gum matrices using freeze-drying. The encapsulated microbeads and microcapsules were evaluated based on encapsulation efficiency (EE), surface charge (zeta potential), microstructure, chemical composition, and thermal properties. Results indicated that Alg-SAPH exhibited a higher EE compared to CSG-SAPH. Alg-SAPH microbeads displayed a more negative zeta potential than CSG-SAPH microcapsules, suggesting enhanced electrostatic stability. Structural analysis revealed that Alg-SAPH formed interconnected microbead chains, whereas CSG-SAPH demonstrated a shell-like morphology. Differential scanning calorimetry (DSC) analysis showed that Alg-SAPH had a lower melting point compared to CSG-SAPH, whereas its transition enthalpy was significantly higher. The findings suggest that encapsulating SAPH within biopolymeric carriers enhances its stability and bioavailability, offering a promising approach for incorporating bioactive peptides into functional foods and therapeutic applications while masking their undesirable taste.